2013
DOI: 10.4102/hsag.v18i1.654
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the uptake of contraception services by Vatsonga adolescents in rural communities of Vhembe District in Limpopo Province, South Africa

Abstract: The aim of the study was to determine the factors that influence the uptake of contraception services by adolescents in the Vhembe district of Limpopo Province, South Africa. A qualitative research method which is explorative, descriptive and contextual in nature was used to investigate the phenomenon from the adolescents’ perspective. The target population comprised of adolescents residing in one of the six villages of Vhembe District. Data was collected through six focus group discussions until data saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 12 publications
2
19
0
6
Order By: Relevance
“…This study, like other previous studies, has established that most parents do not actively participate in the education of their adolescents regarding their sexual and reproductive health [8,9,11]. Although many adolescents will be willing to discuss these issues with their parents, yet, many of them will rather seek information from their peers unless their parents initiate the discussion [12]; but, in cases where the parents are involved, the adolescents made better reproductive health choices [3,24,25].…”
Section: Parental Involvement On Reproductive Health Issuessupporting
confidence: 52%
See 2 more Smart Citations
“…This study, like other previous studies, has established that most parents do not actively participate in the education of their adolescents regarding their sexual and reproductive health [8,9,11]. Although many adolescents will be willing to discuss these issues with their parents, yet, many of them will rather seek information from their peers unless their parents initiate the discussion [12]; but, in cases where the parents are involved, the adolescents made better reproductive health choices [3,24,25].…”
Section: Parental Involvement On Reproductive Health Issuessupporting
confidence: 52%
“…This might be because of the cultural belief in many parts of Africa that open discussion about sexual issues is a taboo. Many respondents (n = 372, 80.5%) indicated that their parents have never initiated discussions with them regarding sexual issues and 348 (78.4%) do not bother to ask their parents about it because 182 felt parents were not supposed to talk about it (43.8%), 162 (38.9%) claimed that it is not culturally acceptable to discuss such matters with their parents while 72 (17.3%) ticked the option of "other reasons" [8,9]. Fig.…”
Section: Sources Of Information Regarding Sexually Transmitted Infectmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Women, however, have limited knowledge of and experience with the 'newer' contraceptive methods. [26,33,34,52,53] Only half of our participants had heard of emergency contraception, the same portion as a study among female university students in 2011, [54] but higher than the 30.0% knowledge found in a Cape Town study of women in public sector clinics in 2004/2005. [53] Clearly, the introduction of LARCs and future multipurpose technologies will require intensive awareness campaigns, encompassing efforts to address health worker misperceptions of these technologies.…”
Section: Researchmentioning
confidence: 58%
“…[30][31][32] Low levels of knowledge and frequent misconceptions about contraception among women of 15 -19 years are particularly concerning. [33,34] These findings cast doubt on how effectively the national Integrated School Health Policy [35,36] is being implemented. The policy recommends that school health services act as a delivery platform for the provision of sexual and reproductive health services, such as contraception and condom distribution.…”
Section: Researchmentioning
confidence: 99%